1998
DOI: 10.1002/(sici)1522-7189(199811/12)6:6<251::aid-nt35>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic profiles of ochratoxin A and ochratoxin α during in vitro incubation in buffered forestomach and abomasal contents from cows

Abstract: Pure ochratoxin A (OA) was added to buffered rumen fluid collected from fistulated cows and incubated under anaerobic conditions. The kinetic pattern of the disappearance of OA and the appearance of ochratoxin α (Oα) was principally the same with four diets fed to donor animals and with three donor animals. The concentration of OA declined to a very low or non‐detectable level with half‐lives at 0.17–1.84 h; its rate of disappearance was first order throughout. The concentration of Oα increased to a constant l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 24 publications
5
22
0
Order By: Relevance
“…This assumption is consistent with results of several in vitro studies with ochratoxin A (Müller et al, 1998(Müller et al, , 2001Özpinar et al, 1999). Müller et al (2001) added pure ochratoxin A to rumen fluid from cows which were fed six diets containing grass, grass silage or hay and two different amounts of concentrate consisting of barley and soyabean meal.…”
Section: Ration Compositionsupporting
confidence: 86%
“…This assumption is consistent with results of several in vitro studies with ochratoxin A (Müller et al, 1998(Müller et al, , 2001Özpinar et al, 1999). Müller et al (2001) added pure ochratoxin A to rumen fluid from cows which were fed six diets containing grass, grass silage or hay and two different amounts of concentrate consisting of barley and soyabean meal.…”
Section: Ration Compositionsupporting
confidence: 86%
“…In contrast to extensive degradation by inoculum from the three forestomach compartments (rumen, reticulum, omasum), no degradation could be shown in vitro with inoculum from the abomasum [68,100,101]. …”
Section: Degradation Of Ochratoxin a In Ruminantsmentioning
confidence: 99%
“…No blocking effect of developing OTα has been shown. The existence of first-order kinetics is explained by the fact that OTA has to pass into the cell to be degraded, and that any such concentration-dependant influx can be considered a first-order process [100]. It has been suggested that little extracellular proteolytic activity contributes to OTA degradation.…”
Section: Degradation Of Ochratoxin a In Ruminantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the capacity to degrade OTA is 20% lower in animals fed a high proportion of concentrates than in animals fed a forage-based diet [31,34,96]. By contrast, other authors found that OTA degradation is accelerated by increasing the content of concentrate in the diet [51].…”
Section: Ruminal Metabolismmentioning
confidence: 99%